Population Migration as a Risk Factor of Transboundary Importation of Dangerous Infectious Diseases in the Siberian and Far Eastern Federal Districts - A. K. Noskov; V. A. Vishnyakov; M. V. Chesnokova; S. A. Kosilko; S. V. Balakhonov (Эпидемиология и вакцинопрофилактика, 2015)
Some kinds of external migration of the population are considered as a risk factor for occurrence of the epidemic foci of dangerous infectious diseases in Siberian and Far Eastern Federal Districts of the Russian Federation. The role of tourism and labour transboundary migration in formation of epidemic complications for dangerous infectious diseases is shown. The urgency of threats for the disease importations representing danger to humans including influenza caused by a new virus subtype, measles, cholera, poliomyelitis and Dengue fever etc increases in the given regions.